TO THE ISSUE OF UKRAINIAN MODERN: EARLY MODERN PROBLEMS OF TOLERANCE - Yosypenko, Serhii (Sententiae, 2008)
In the process of «secularizing» the problems of faith unity, church unity|ecclesia|, change into the question of political unity. However, for the making of positive|staid| cocept| of tolerance the cultural|gracious| changes and change|changing| of dominating|mainstream| ideas are needed, but not only changes in the political sphere. These changes in a western modern culture are concentrated around|around| the correlation problems of: a|but|) earthly and celestial into religion and in its relationships with the world; b|) temporal|secular| and spiritual|spirit| powers| on the earth|ground-to-air|; c) religion unity and multiplicity of its displays. Understanding of these correlations already on the modern principles means reducing interaction| of religious and political spheres, assertion of the religiousness, which depend on exceptionally|only| against force|strenth| of Word|wd|, but not states. Opening of modern policy|politics| new|firsttime| quality stimulates “overopening|” of religious principles: both processes|Carbro| can be observed on the example of those “secularing|” and “church” theologies which|what| is created in Ukraine on the fracture|breaking| of XVII-XVIII| ages|century| and which|what|, together with appearance|occurring| of new|firsttime| theories and practices of human conduct in the world, become|stand| the determining|attributive| steps|footpace| of Ukrainian modernity development. References